Exploring gas-phase plasma chemistry and plasma-surface interactions: progress in plasma-assisted catalysis - Hanna, Angela R., author; Fisher, Ellen R., advisor; Levinger, Nancy E., committee member; Rappe, Anthony, committee member; Bradley, R. Mark, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: plasma chemistry